Ifo World Economic Survey June 2002 - Gernot Nerb; Anna Stangl (Ifo World Economic Survey, 2002)
World Economic Climate soared in April - Economic expectations picked up further - Inflation in 2002 expected to be only slightly lower than in 2001 - Short and long-term interest rates expected to rise - Euro expected to strenghten - Stronger corporate governance requested
Keywords: 330